Stakeholder engagement in European research and innovation: An investigation into how and why EU R&I projects develop engagement tools [version 1; peer review: 2 approved, 1 approved with reservations] - Luka Gudek; Jacqueline Broerse; Madhura Rao (Open Research Europe)
Background The European Union’s research and innovation (R&I) efforts have increasingly prioritised collaboration, co-creation, and stakeholder engagement to address complex systemic challenges in recent decades. However, while stakeholder engagement has become a cornerstone of EU innovation policy in this area, there has been limited research into how tools supporting stakeholder engagement are developed, deployed, and sustained within R&I projects. To address this gap, this article explores factors influencing the development of stakeholder engagement tools in European R&I projects and their relation to the broader European R&I trends. Methods This study adopts a qualitative approach, with conducting semi-structured interviews with 22 participants representing 14 Horizon Europe projects on topics of agri-food, bioeconomy, and sustainability. Data were collected, coded, and analysed concurrently and the emerging results guided which group was approached next. Results Tools developed within projects take up shape within distinct phases, denominated as Purpose, Prototyping, Praxis, and Post-project continuity. Each of these phases comes with distinct challenges and opportunities. The way projects approach these challenges and opportunities showcases two distinct approaches that might be indicative of broader project management work in European R&I projects. These are the Project-focused approach and the User-focused approach. Conclusions This study contributes to the broader discourse on sustainability innovation by providing empirical insights into the mechanisms and dynamics of stakeholder engagement tools in R&I projects. It underscores the importance of balancing structural R&I frameworks with flexible, participatory approaches to innovation. The findings offer actionable recommendations for policymakers, project coordinators, and funders to support the development of robust and inclusive stakeholder engagement tools that mobilise diverse actors and facilitate systemic change aligned with the EU’s sustainability goals.